2007
DOI: 10.3141/2016-06
|View full text |Cite
|
Sign up to set email alerts
|

Initial Findings on Skid Resistance of Unpaved Roads

Abstract: Unpaved roads have a dynamic surface, which can make it difficult to predict the skid resistance of a section for use in geometric design and gravel selection and to schedule maintenance. This investigation showed that there are three mechanisms for skidding on unpaved roads: intersurface friction, sliding on a thin layer of loose material, and plowing through a thick layer of loose material. The main surface and material properties affecting skid resistance are the stoniness severity and extent, the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Lea (5) was thus an initial investigation into the skid resistance of gravel roads during braking, with the aim of determining ranges of expected coefficients of friction and determining what, if any, material or surfacing properties affected the measured skid resistance of a section. The effects of moisture and vehicle speed also were investigated.…”
Section: Initial Findings On Skid Resistance Of Unpaved Roadsmentioning
confidence: 99%
“…Lea (5) was thus an initial investigation into the skid resistance of gravel roads during braking, with the aim of determining ranges of expected coefficients of friction and determining what, if any, material or surfacing properties affected the measured skid resistance of a section. The effects of moisture and vehicle speed also were investigated.…”
Section: Initial Findings On Skid Resistance Of Unpaved Roadsmentioning
confidence: 99%
“…The plowing component is the interaction of a tire moving through a thick layer of loose material. While Lea and Jones (2007) give various drag relationships with the above three factors, they are not statistically significant enough to provide reliable skid resistance measurements. Further work is needed to confidently write the skid resistance on soil surfaces.…”
Section: Friction On Unpaved Soil Surfacesmentioning
confidence: 95%
“…A preliminary look at the skid resistance on soil surfaces was later conducted by (Lea and Jones 2007) and found that the skid resistance on a soil surface depends on three key factors: inter-surface friction, sliding, and plowing. The inter-surface friction component is the familiar interaction of a tire with a rigid surface in which the surface texture is the dominant factor.…”
Section: Friction On Unpaved Soil Surfacesmentioning
confidence: 99%
“…All these models have traffic volume, plasticity index, various components of the particle size distribution, curvature, grade, and rainfall or season as input variables. In addition, models to predict shape and slope loss (17) and to estimate friction (18,19) were developed, while relationships to predict dust are also available (20).…”
Section: Relevant Properties Of Unsealed Roadsmentioning
confidence: 99%